Analysis of Interference Models a Social Linguistics Research: Empirical Study of Students - Repki Repki; Muhammad Fuad; Sumarti Sumarti; Nurlaksana Eko Rusminto; Siti Samhati; Dimas Ade Chandra (Yayasan Keluarga Guru Mandiri, 2025)
This research aims to discover the causes of interference among students at Swadhipa 2 Natar Vocational School and to prove the initial hypothesis that some students at Swadhipa 2 Natar Vocational School often experience interference phenomena in communicating. This research uses a qualitative descriptive method, with data collection techniques through observation and interviews. The observations carried out were by direct observation of students who were indicated to frequently mix their first language with their second language both in class and outside of class. The results of this research show that students who often mix elements of their mother tongue in their speech are students who come from one area, namely Pejambon Village. The main factor in interference is the habit at home and socializing in the environment of using the mother tongue dominantly so that mastery of the second language is less mastered.